What does the future hold? Historical climate analysis and projection of future climatic scenarios for the andean canton of Pedro Moncayo, Ecuador - Cáceres-Arteaga, Natali; Ayala-Campaña, Oscar; Rosero-Vaca, Darwin; D. Lane, K. Maria (Revista Geográfica de América Central., 2018)
The natural and anthropogenic variations of climate systems are increasingly evident. Climate change has become the central theme of research for decision making at all levels. The principal objective of the current research is to identify the evidence of change in certain climatic elements, such as precipitation and temperature at the local scale in Pedro Moncayo, Ecuador. The study uses records from 1981-2017 produced by 126 meteorological stations of the National Institute of Meteorology and Hydrology closest to the study area. Geographical Information Systems were used for statistical analysis and geographical representation. This is the first study that presents climate scenarios at local scale in Ecuador, It aims to be a contribution for the scientific community, but especially for vulnerable communities in their planning processes and strengthening their adaptation capacity.